2019
DOI: 10.1136/acupmed-2017-011445
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of efficacy of acupuncture in the management of low back pain: a systematic review and meta-analysis of randomised placebo- or sham-controlled trials

Abstract: Objectives: To assess the evidence for the efficacy of acupuncture for non-specific low back pain (NSLBP), compared with sham or placebo therapies. Methods: We searched Cochrane CENTRAL to December 2016, and conducted searches from 1980 to December 2016 in PubMed, MEDLINE and Embase. There were no regional restrictions applied. We included only randomised controlled trials of adults with NSLBP. Placebo/sham procedures were required of the control interventions. The trials were combined using meta-analysis when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 30 publications
1
18
0
2
Order By: Relevance
“…Integration of acupuncture into clinical pain management is expanding rapidly due to the effort of reducing reliance on traditional analgesics. Mounting evidence supports the analgesic effect of acupuncture in the diseases such as low back pain, neck pain, cancer pain et al [ 12 , 31 , 32 ]. However, a randomized controlled trial (RCT) study about EA relieving FBSS symptoms has not been reported.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Integration of acupuncture into clinical pain management is expanding rapidly due to the effort of reducing reliance on traditional analgesics. Mounting evidence supports the analgesic effect of acupuncture in the diseases such as low back pain, neck pain, cancer pain et al [ 12 , 31 , 32 ]. However, a randomized controlled trial (RCT) study about EA relieving FBSS symptoms has not been reported.…”
Section: Discussionmentioning
confidence: 97%
“…In recent years, acupuncture has been used as an integrative therapy for pain since well-tolerated with little risk of adverse effects [ 11 ]. Numerous systematic reviews have investigated that acupuncture has a therapeutic effect on chronic low back pain [ 12 , 13 ]. And the mechanisms of acupuncture analgesic effect were reported to involve endogenous pain control systems, cerebral plasticity, and nonspecific effects [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…ATP released by AP/EAP may cause analgesia both by acting indirectly via the release of adenosine, or directly via stimulating P2X3 or P2X7Rs in the periphery or along the central pain-conducting pathways ( He et al, 2020 ). EAP has been shown to alleviate pain and downregulate the previously increased P2X3R protein and P2X3R current amplitudes in acutely dissociated DRGs prepared from rats which underwent chronic constriction injury of their sciatic nerves (the neuropathy model; Tu et al, 2012 ; Wang et al, 2014 ; Liang et al, 2019 ; Du et al, 2020 ) or received CFA injection into their paws (the inflammatory pain model; Xiang et al, 2020 ). Similarly, the chronic constriction injury– or neck incision–induced pain and the accompanying spinal overexpression of inflammatory cytokines (as typical responses to P2X7R stimulation) as well as increase in P2X7R mRNA were sensitive to EAP ( Xu et al, 2016 ; Gao et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Acupoints are certain acupuncture-sensitive points, the stimulation of which changes the flow of the life energy Qi through the 12 meridians believed to regulate health state according to TCM. Although in the clinical praxis, AP is a means of treating low back pain ( Berman et al, 2010 ; Xiang et al, 2020 ), chronic neck pain ( Seo et al, 2017 ), musculoskeletal pain ( Yuan et al, 2016 ), migraine ( Pei et al, 2019 ), as well as visceral ( Lee et al, 2019 ) and cancer pain ( Chiu et al, 2017 ), the evidence for its efficiency is, in spite of conducting sham-controlled randomized trials and meta-analyzes even deposited in the Cochrane database, far from being unequivocal. The cautious assessment of the results is based on the following considerations ( Madsen et al, 2009 ; Colquhoun and Novella, 2013 ): 1) large multicenter clinical trials consistently revealed that the true (verum) and sham AP (stimulation at nonspecific acupoints) do not differ in their effectiveness in decreasing pain levels across multiple chronic pain disorders; 2) the existing differences between AP (verum or sham) and non-AP groups in improvement were only minor; 3) it is hard to understand why AP relieves some types of pain while leaving other types of probably similar etiology unaffected; and 4) interestingly, the strongest evidence for a positive outcome of AP treatment is in case of postoperative nausea and vomiting, conditions not related to pain ( Tang et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Houve manipulação espúria na diretriz clínica para dor lombar do The National Institute for Health and Care Excellence (NICE) 33,34 de 2016 e 2018. A acupuntura mostrava-se eficaz em ensaios clínicos 35 e revisões 36,37 Porém, a diferença pequena entre acupuntura e sham (frente ao critério de MID adotado) eliminou a acupuntura (lado direito da Figura 1) da diretriz, que é considerada de alta qualidade 39 . O padrão de MID foi aplicado de forma desigual e inconsistente, rigidamente na acupuntura e vagamente para outras intervenções 34 .…”
Section: P4 E a Eficácia Dos Cuidados Com Picsunclassified